2006
DOI: 10.1248/bpb.29.911
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio vulnificus Vulnibactin, But Not Metalloprotease VvpE, Is Essentially Required for Iron-Uptake from Human Holotransferrin

Abstract: Vibrio vulnificus is a gram-negative halophilic estuarine bacterium. The pathogen causes fatal and rapidly-progressing septicemia with high mortality. This V. vulnificus septicemia (VVS) is closely associated with the consumption of raw seafood contaminated with the bacterium in patients with underlying hepatic disease, heavy alcohol-drinking habits, or other immunocompromised conditions. Several putative virulence factors including capsule, hemolysin, protease, and iron-assimilation systems have been suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…The primary system used by this organism involves siderophores, of which V. vulnificus produces two types: a catechol and a hydroxymate (141). The catechol siderophore (vulnibactin) is the chief means by which V. vulnificus acquires iron and is required for growth in iron-limited media (1,61). Mutational analysis of genes involved in vulnibactin synthesis and transport has demonstrated that this siderophore is also required for scavenging iron from transferrin and holotransferrin (61,157).…”
Section: Iron Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary system used by this organism involves siderophores, of which V. vulnificus produces two types: a catechol and a hydroxymate (141). The catechol siderophore (vulnibactin) is the chief means by which V. vulnificus acquires iron and is required for growth in iron-limited media (1,61). Mutational analysis of genes involved in vulnibactin synthesis and transport has demonstrated that this siderophore is also required for scavenging iron from transferrin and holotransferrin (61,157).…”
Section: Iron Acquisitionmentioning
confidence: 99%
“…The catechol siderophore (vulnibactin) is the chief means by which V. vulnificus acquires iron and is required for growth in iron-limited media (1,61). Mutational analysis of genes involved in vulnibactin synthesis and transport has demonstrated that this siderophore is also required for scavenging iron from transferrin and holotransferrin (61,157). The suspected role of vulnibactin in virulence was confirmed through mutation of several vulnibactin-associated genes (vuuA, venB, vvsA, and vvsB), which resulted in diminished virulence compared to wild-type strains (64,94,157).…”
Section: Iron Acquisitionmentioning
confidence: 99%
“…These genes encode proteins involved in iron acquisition systems. V. vulnificus utilizes vulnibactin (catechol sidephore) as its main pathway for iron acquisition (Alice et al, 2008;Kim et al, 2006). Previous work that applied mutational gene experiments showed that mutation of vuuA resulted in reduced virulence compared with a wildtype strain (Webster & Litwin, 2000).…”
Section: Clusters Of Orthologous Groups (Cog) Functional Categories Omentioning
confidence: 99%
“…Bt1 strains use vulnibactin for scavenging iron from human transferrin (Tf) both in vitro and in vivo (in mice, the animal model for human vibriosis). Thus, Bt1 mutants deficient in vulnibactin production or in the vulnibactin receptor (VuuA) grow less efficiently in iron-deficient media and are attenuated in mouse virulence (25)(26)(27). In addition, V. vulnificus Bt1 can utilize non-Tf-bound iron through a heme receptor, HupA, also involved in virulence for mice (28,29).…”
mentioning
confidence: 99%